ECHOCARDIOGRAPHIC PROFILE OF RHEUMATIC HEART DISEASE AT A TERTIARY CARDIAC CENTRE - Aurakzai, Hamza Arslan; Hameed, Shahid; Shahbaz, Ahmad; Gohar, Salman; Qureshi, Moqueet; Khan, Habibullah; Sami, Waqas; Azhar, Muhammad; Khan, Jawad Sajid (Journal of Ayub Medical College Abbottabad, 2009)
Background: Rheumatic Heart Disease (RHD) continues to be a major public health problem in developing countries like Pakistan. Objective of this cross sectional-analytical study was to analyze the severity of valvular lesions on echocardiography in patients pre-diagnosed with RHD. Methods: The transthoracic echocardiographic records of RHD patients from 2004 to 2008 were retrospectively reviewed for type and degree of valvular involvement according to AHA/ACC guidelines. Results: A total of 13,414 patients [7,219 Males (53.8%), 6,195 Females (46.2%)] ranging from 11 to 90 years with a mean age of 42.33±18.976 were studied. On echocardiography, 7,500 (56%) had mitral regurgitation (8.8% severe MR), 6,449(48.2%) had tricuspid regurgitation (7.1% severe TR) and 5,550 (41.4%) had aortic regurgitation (4.8% severe AR). MS was detected in 2,729 (20.3%) patients (15.3% severe MS), AS in 102 (0.8%) and TS in 31 (0.2%) patients. Mixed mitral valve disease was seen in 3,185 (23.7%), mixed aortic valve disease in 222 (1.7%) and mixed tricuspid valve disease in 47 (0.4%) patients. All three valves were involved in 2,826 (21.06%) patients, combination of mitral and aortic valves in 3,103 (23.13%), mitral and tricuspid in 3,784 (28.2 %), and mitral only in 3,701 (27.59%) patients. There was some mitral valve abnormality in all patients. Conclusion: Mitral valve was most commonly affected, while regurgitant lesions were more common than stenotic lesions, and most severe in younger patients. All valvular lesions had almost an equal distribution among the sexes, except aortic regurgitation, which was more common in females. Therefore, echocardiography should be done routinely for patients with RHD, focusing on younger population, to facilitate diagnosis and definitive treatment before complications set in. Keywords: Rheumatic heart disease, Echocardiography, Valvular heart disease